Lesson learned in pediatric haploidentical transplantation in a low-resource environment: delivering melphalan IV and using low dose radiation reduce graft failure - Valentine Jiménez-Antolinez; Julia Colunga-Pedraza; Andrés Gómez-De León; Elias González-Lopez; David Gómez-Almaguer; Oscar González-Llano (Hematology)
Objectives: Primary graft failure (pGF) after hematopoietic stem-cell transplant is associated with considerable morbidity and mortality. The incidence in haplo-HSCT has been reported to be between 0% and 30%. In 2018, we identified a pGF incidence of 35% in our pediatric haplo-HSCT recipients with hematologic malignancies, which motivated us to enact changes to the conditioning regimen.Methods: We performed a single-center prospective, pre–post study of consecutive patients under 16 years with hematologic malignancies, from January 2015 to December 2022 who received a haplo-HSCT. Twenty-six pediatric patients received a haplo-HSCT before September 2018 (G1) and 36 patients after (G2). The main conditioning regimen for G1 was myeloablative with Flu/Cy/Bu, and for G2 the main regimen was reduced intensity Flu/Cy/Mel/TBI2.Results: Nine patients (35%) in G1 had primary graft failure, while in G2 there were no patients with pGF. The median follow-up for G1 was 15.9 months, and for G2 was 24.8 months, with an estimated overall survival at 12 months of 63% (95% CI 47–76) versus 85% (95% CI 73–93), and at 24 months of 47% (95% CI 31–64) versus 70% (95% CI 54–82) respectively (p = .007).Conclusion: After September 2018 conditioning regimen modifications were implemented with the objective of reducing primary failure, consisting mainly of switching from busulfan to melphalan as the alkylating agent of choice, and adding, when clinically possible TBI. Primary failure has been significantly reduced in our institution since then.